QUBIC: The Q&U Bolometric Interferometer for Cosmology - A novel way to look at the polarized Cosmic Microwave Background - Mennella, Aniello (2018)
In this paper we describe QUBIC, an experiment that takes up the challenge posed by the detection of primordial gravitational waves with a novel approach, that combines the sensitivity of state-of-the art bolometric detectors with the systematic effects control typical of interferometers. The so-called "self-calibration" is a technique deeply rooted in the interferometric nature of the instrument and allows us to clean the measured data from instrumental effects. The first module of QUBIC is a dual band instrument (150 GHz and 220 GHz) that will be deployed in Argentina during the Fall 2018.